RECOMMENDATIONS FOR THE DEVELOPMENT OF REGULATORY GUIDELINES FOR REGISTRATION OF TRADITIONAL MEDICINES IN SOUTH AFRICA - Ngcobo, Mlungisi; Nkala, Bongani; Moodley, Indres; Gqaleni, Nceba (African Journal of Traditional, Complementary and Alternative Medicines, 2011)
The regulation and registration of traditional medicines (TM) continues to present challenges to many countries regardless of the fact that an increased number of the population utilises TM for their health care needs. There have been improvements in the legal and policy framework of South Africa based on the WHO guidelines. However, there are currently no guidelines or framework for the registration of TM in South Africa. This article reviews literature and existing guidelines of specific countries and regions and makes recommendations for South African guidelines.